1987
DOI: 10.1159/000118355
|View full text |Cite
|
Sign up to set email alerts
|

Drug Influences on Learning and Memory in Aged Animals and Humans

Abstract: In this article the effects of neurotransmitter systems or specific drugs on cognitive functions of aged animals and humans are reviewed. While there have been used many different pharmacologic and behavioral approaches to treat and test cognitive deficits in aged animals and geriatric or demented patients, there is still the question of the validity of animal models of human disorders. Attempts are made to show that there are parallels and similarities. These similarities suggest that the neurological and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…The finding that SP enhanced water maze performance in old rats provides further evidence for the hypothesis that age-related performance decrements, especially based on learning and memory deficits, may be restored by treatment with neuropeptides (De Wied and van Ree 1982;Hock 1987). Attenuation of agedependent impairment on learning and memory tasks has already been reported for the ACTH-analog Org 2766 (Rigter et al 1984) and vasopressin (Cooper et al 1980).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The finding that SP enhanced water maze performance in old rats provides further evidence for the hypothesis that age-related performance decrements, especially based on learning and memory deficits, may be restored by treatment with neuropeptides (De Wied and van Ree 1982;Hock 1987). Attenuation of agedependent impairment on learning and memory tasks has already been reported for the ACTH-analog Org 2766 (Rigter et al 1984) and vasopressin (Cooper et al 1980).…”
Section: Discussionmentioning
confidence: 63%
“…Thus, it is possible that the enhancing effect of SP on performance was a result of a central action of the peptide. In particular, central vasodilatatory effects of SP must be considered as one possible mechanism of action (Klugman et al 1980;Edvinsson et al 1982) because several drugs known to facilitate learning in aging animals are vasodilatators (Hock 1987). Since SP may be enzymatically cleaved into active fragments prior to exertion of its action (Krause 1985), it would be important to know whether SP itself or a certain sequence of the molecule accounts for its effects, as seems to be the case for its reinforcing action (Oitzl et al 1990) and its effects on avoidance learning (Hasen6hrl et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the active avoidance tests, EE-SHT did not influence CAR, an active memory guided response, indicating that EE-SHT has no direct memory improving effects in normal animals. Many memory impairment models have been established and used in the studies of memory and learning process (Hock, 1987;Kucharski and Hall, 1987). Five of such models were used in this work: 30% ethanol-induced and scopolamine-induced memory restriction deficit mice, 40% ethanol-induced memory retrieval impairment mice, ECS-induced memory consolidation deficit mice and ECS-induced memory retrieval deficit mice.…”
Section: Discussionmentioning
confidence: 99%
“…This unique combina tion of actions led us to suppose that FR64822 may inter act with some other endogenous substance that has erec tile response stimulating, memory improving and body weight reducing activities. In support of this assumption, several lines of evidence suggest that a number of endo genous substances such as acetylcholine, serotonin, vaso pressin and adrenocorticotropin play an important role in the control of memory formation (20,21) as well as self grooming behaviors (18,(22)(23)(24). It has also been reported that some of these substances may be involved in the control of appetite (25,26).…”
Section: Discussionmentioning
confidence: 92%